Impact of blended learning on studying English as a Foreign Language - Holovatska, Nataliia (East European Journal of Psycholinguistics, 2023)
The paper focuses on the research of the efficiency of three primary forms of teaching and besides, blended learning influence on learning and teaching English as a foreign language at Yuriy Fedkovych Chernivtsi National University, Ukraine, at Faculties of Economics (particularly, Economic Cybernetics), Law, Pedagogy and Psychology, Philology, for two academic years 2020/2021, 2021/2022. The study sample consisted of 120 students from 4 mentioned faculties who took the compulsory academic discipline English for Specific Purposes in the 1st, 2nd and 3rd semesters in compliance with their curriculum. The objectives of the study are to analyze and compare the effectiveness of the practical application of the three primary forms of education (full-time, distant and blended) and to study the impact of blended learning on teaching and learning English as a foreign language in practical classes of the compulsory English course. For the research, a questionnaire survey divided into two parts was used. Each of the survey parts included four items. The second part of the survey was conducted based on the typical 5-level Likert scale. To analyze the elicited data, SPSS (Statistical Package for the Social Sciences) program was used for the qualitative research. The outcomes in both parts are presented in percentages. The study conclusions showed that a blended study is the challenge of the present-day education system and is highly approved by university students. They are sure that using blended learning in teaching EFL at Chernivtsi National University is beneficial, advantageous and productive for improving skills in English as a foreign language course. Four-fifths of the respondents stated that their language proficiency skills significantly enhanced compared to conventional teaching methods. Author: Nataliia Holovatska 0000-0002-2051-9454 n.holovatska@chnu.edu.ua